Meningkatkan Antusiasme Peserta Didik dalam Mengikuti Layanan Bimbingan Klasikal dengan Menggunakan Media Permainan “SATAKA TESA” - Aprilia Devi Nur Habibah; Intan Prastihastari Wijaya; Ayu Febri Eka Putri (CV. ITTC INDONESIA, 2025)
This study aims to enhance students’ enthusiasm and participation in classical guidance services through the implementation of game-based learning media in class X-X of SMAN 7 Kediri. Reserach method of this study is Classroom Action Research (CAR), which consists of three stages: pre-cycle, Cycle I, and Cycle II. In the pre-cycle stage, the guidance services were still delivered through an expository lecture method without any interactive supporting media, resulting in low student engagement. In Cycle I, the researcher implemented the game “3 Magic Words,” which focused on the use of the words “please,” “sorry,” and “thank you” to foster communication ethics. The results showed an increase in participation from 70.96% to 74.78%. In Cycle II, a new variation of the game was introduced, namely “Mutual Puzzle,” which emphasized teamwork, communication, and empathy. The results of Cycle II showed a significant increase to 82%, indicating the effectiveness of this approach. The findings of this study reveal that the use of game-based media can create a more interactive and enjoyable learning environment, encouraging active student engagement in classical guidance services.